Engaging in emotional labour when facing customer mistreatment in hospitality - Simillidou, Aspasia; Christofi, Michael; Glyptis, Loukas; Papatheodorou, Andreas; Vrontis, Demetris (My University, 2020)
Emotional labour (EL) is a self-controlling process during which employees monitor and regulate their moods and expressions when interacting with customers. Such self-monitoring takes place through employees engaging with either deep acting (DA) or surface acting (SA) EL strategies. Although empirical evidence indicates that employees are capable of deploying both strategies, it acknowledges a predominant use of SA when employees deal with aggressive customers, something which in turn creates resource-depleting effects. Nevertheless, there is lack of a holistic understanding of the conditions under which employees engage in either strategy. Also, research is inconclusive on the negative effects of SA; how these can be overcome; whether the means for overcoming these effects associate with the deployment of DA; and what the effects of DA are in conditions of customer mistreatment. Motivated by the above knowledge gap, we drew on contagious emotions, affective events and emotional labour and emotional intelligence theories to conduct 70 in-depth, semi-structured interviews within the hotel industry. While findings confirm extant research on the conditions that lead to the deployment of SA and its effects to employee welfare and performance, they contribute that the means used to overcome the negative effects of SA, stimulate the development of conditions that lead the way to the deployment of DA. The study also contributes positive organisational and employee effects from applying DA in aggressive customer contexts, which reinforce the very conditions that enable it.
Keywords: Affective events; Contagious emotions; Deep acting; Emotional intelligence; Emotional labour; Surface acting